Iot-Based Real-Time Landslide Detection Using Fuzzy Logic - Nur Tihani Faqihah, Nuruddin Kamal (2023)
The goal of this senior project is to create a smart landslide detection system that will provide early warning and landslide mitigating measures. Effective monitoring and detection systems are required because landslides represent a serious hazard to infrastructure, human lives, and the environment. To build a reliable and intelligent system, the project makes use of cutting-edge technology including IoT (Internet of Things), data analytics, and fuzzy logic. The project starts with a thorough assessment of the approaches, technologies, and literature related to landslide detection. The project pinpoints the weaknesses and restrictions of the existing systems through this evaluation and suggests creative solutions to deal with these issues. The system design consists of a network of sensors, strategically placed in landslide-prone locations, including rain gauges, soil moisture sensors, accelerometers, and tilt sensors. The initiative also stresses the value of early warning systems and mitigation plans. The technology automatically informs and notifies the appropriate authorities, emergency response teams, and local populations if a potential landslide is detected. This makes it possible to quickly evacuate and to put mitigation measures in place to lessen the effects of landslides. The results of this study will have a big impact on people living in landslide-prone regions, urban planners, and disaster management organisations. The created system offers a trustworthy and effective instrument for landslip early detection, warning, and mitigation, improving public safety and lowering the potential harm brought on by these natural hazards.